Influence of cardiolipin remodeling on mitochondrial respiratory function in the heart - Le, Catherine Hoang, author; Chicco, Adam J., advisor; Bouma, Gerrit J., committee member; Hamilton, Karyn L., committee member; Pagliassotti, Michael J., committee member (Colorado State University. Libraries, 2013)
The following investigation comprises a series of experiments with the overall aim of elucidating the role of cardiolipin acyl-chain remodeling on mitochondrial respiratory function in the mammalian heart. The experiments tested the general hypothesis that changes in the fatty acid composition of cardiolipin, a unique mitochondrial phospholipid, contribute to cardiac mitochondrial respiratory dysfunction, which is believed to be an underlying mechanism of myocardial hypertrophy and contractile dysfunction in several cardiac pathologies. The specific aims of each experimental series were to: 1) Determine the influence of cardiolipin compositional changes on cardiac mitochondrial respiratory function in models of aging, pressure overload hypertrophy and heart failure, and 2) Determine how defects in the cardiolipin remodeling process itself elicits cardiac mitochondrial respiratory dysfunction associated with a genetic childhood-onset cardiomyopathy, known as Barth syndrome. Studies in Aim 1 demonstrated that the distinct pattern of aberrant cardiolipin remodeling observed in the aged and failing heart resulted from increased metabolism of polyunsaturated fatty acids (PUFAs), which predominate in the cardiolipin molecular species. Pharmacological inhibition of delta-6 desaturase, the rate-limiting enzyme in the PUFA metabolism pathway, reversed cardiolipin remodeling, reduced myocardial hypertrophy and preserved contractile function in the rodent models of aging, pressure overload and hypertensive heart disease. However, in contrast to our hypothesis, reversal of these changes in cardiolipin composition did not have a significant effect on mitochondrial respiratory function, dissociating alterations in cardiolipin composition from cardiac mitochondrial respiratory dysfunction in these conditions. Studies in Aim 2 demonstrated a marked substrate-specific impairment of cardiac mitochondrial respiratory function in mice lacking the cardiolipin remodeling enzyme, tafazzin. Cardiac mitochondria from tafazzin-deficient mice demonstrated a selective impairment in carbohydrate and lipid oxidation and a dramatic decrease in pantothenic acid amounts. These data suggest a role of tafazzin in the transport, activation, and/or generation of reducing equivalents by the TCA cycle. Additionally, these data implicate impairment of tafazzin function and/or cardiolipin remodeling process itself, rather than alter cardiolipin composition per se, in mitochondrial dysfunction associated in Barth syndrome. Collectively, these findings challenge previous studies suggesting that alterations of the distinctly uniform acyl-chain composition of cardiolipin impair cardiac mitochondrial respiration. Rather, they instead show that the widely observed redistribution of cardiolipin PUFA content in chronic cardiac pathologies appears to reflect a global increase in PUFA metabolism that profoundly influences cardiac structure and function by mechanisms we are only beginning to understand. Interestingly, the cardiolipin remodeling process itself and/or tafazzin enzyme may play a more important role than previously thought in cardiac mitochondrial respiratory function and cardiomyopathy.
Keywords: disease; mitochondria; lipids; heart